Poder local e Organizações Não-Governamentais (ONGS) no Nordeste brasileiro : o caso de Lagoa Seca, PB (1994 a 2006) - Campos, Nivalda Aparecida (2009)
This research focuses on the way local institutional political power relates to new institutional actors, especially non governmental organizations (NGOs), in a northeastern town in the state of Paraiba, between 1994 and 2006. We analyzed the relationship between the social actors, who represent a new model of state administration also known as non-state public sector on one side, and political leaderships on the other side, in a given region in the country, many times far from large decision-making centers not only in geographical aspects but also in terms of relevant social-indicators, and that allows us to realize the socioeconomic aspects of the composition and organization of the social space.The evidence of conflict between NGOs and local political power attracted attention and led to this research which takes into consideration that one of the questions that permeates the performance of both parties, though in a distinguished manner, is the approach to droughts, an issue historically addressed by the State.